#TITLE_ALTERNATIVE# - RAHMAN (NIM 12206056): Pembimbing: Dr. Ir. Sudjati Rachmat, DEA., HIBATUR
Hydraulic fracturing is the making of fracture with direction that extends from the well hole which has a higher conductivity than the conductivity of the reservoir. In general, hydraulic fracture stimulation performed in wells with low permeability, but at the recently conducted also on the well with large permeability with tip screen out method (TSO). Determination of fracture half-length (Xf) is the key to success in hydraulic fracturing operations. Therefore in this final assignment will discuss the determination of fracture half-length by considering its economic factor. The stages in the fracture half-length determination including the selection of candidates reservoir, reservoir modeling, fracture geometry utilization, fracturing fluid utilization, proppant utilization, and its economic calculations. After performing injection flow rate and fracture half-length sensitivity, the design fracture half-length of 250 ft with the flow rate injection of 24 bbl /min provides the largest net present value (NPV).